SYNTHESIS AND DFT QUANTUM CHEMICAL CALCULATIONS OF PYRAZOLE SCAFFOLD PYRIMIDINE DERIVATIVES - Sivalingam Lakshmanan (International Journal of Modern Agriculture, 2020)
In this study, a suitable procedure for the preparation of pyrazolo[1,5-c]pyrimidin-7(1H)-one derivatives is described.. The structures of the synthesized compounds (2a, b) were characterized by elemental analysis, FT-IR, 1H and 13C-NMR spectroscopic techniques. In addition to experimental study in order to find molecular properties, quantum-chemical calculations of the new pyrazolo[1,5-c]pyrimidin-7(1H)-one derivatives (2a, b) were carried out by using DFT/B3LYP method with the 6-311G(d,p) and 6-311++G(2d,2p) basic sets.